Mechanism of modulation through PI3K-AKT pathway about Nepeta cataria L.’s extract in non-small cell lung cancer - Fan, Jiaxin (Oncotarget, 2017)
Non-small cell lung cancer (NSCLC) is regarded as one of the major intractable diseases, which was cured mainly by chemotherapeutics in the clinical treatment at present. But it is still a vital mission for the current medical and researchers that hunting a natural medicine which have little side effects and high-efficiency against the NSCLC on account of the shortcomings on current drugs. Nepeta cataria L. plays an important role in anti-cancer treatment according to the reports which was recorded in the Chinese Pharmacopoeia of version 2015 and belongs to one of the Traditional Chinese medicine (TCM). Microfluidic chip technology is widely used in scientific research field due to its high-throughput, high sensitivity and low cost with the continuous progress of science and technology. In this study, we investigate the effect of total flavonoid extracted from Nepeta cataria L. (TFS) through human lung cancer cell line A549 based on the microfluidic device and Flow Cytometry. So we detected the mRNA expression of MicroRNA-126 (miR-126), VEGF, PI3K, PTEN and proteins expression respectively to explore the partial PI3K-AKT pathway molecular mechanisms through Quantitative Real-time PCR (qRT-PCR) and Western Blot. The results showed that TFS can disturb the expression of miR-126 and regulate the PI3K-AKT signaling pathway to meet the effect of anti-cancer. Taking all these results into consideration we can draw a conclusion that TFS may be used as a novel therapeutic agent for NSCLC in the near future.